Evaluation of the Performance of QuantiFERON-TB Gold Plus Assay in Human Immunodeficiency Virus Infection - Melike YAŞAR DUMAN; Cengiz ÇAVUŞOĞLU; İmre ALTUĞLU; Ayşin ZEYTİNOĞLU; Ayşe Deniz GÖKENGİN; Tansu Gülbahar AYDOĞAN; Mehmet Nurullah ORMAN (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: Individuals co-infected with human immunodeficiency virus (HIV) and Mycobacterium tuberculosis have an increased risk of the reactivation of latent tuberculosis (TB) infection (LTBI) to active TB. The addition of peptides to stimulate CD8+ T cells is expected to increase the sensitivity of the QuantiFERON®-TB Gold Plus (QFT-Plus) assay in detecting LTBI and TB infection in patients. This study aimed to determine the prevalence of LTBI in patients with HIV infection in our region and to evaluate the possible factors that may interfere with the performance of the QFT-Plus assay in HIV infection. Materials and Methods: The study included 132 HIV-positive and 133 HIV-negative cases presented to the Ege University Medical Faculty Hospital between January 2016 and December 2019. Demographic and clinical data and laboratory/culture results were obtained from the mycobacteriology laboratory and hospital database. Results: QFT-Plus positivity rates were 30.1% (40/133) in the HIV-negative and 21.2% (28/132) in HIV-positive groups. The indeterminate results of the HIV-positive and HIV-negative groups were 4.5% and 3%, respectively. The CD4+ T cell count was below 200/mm3 in five of the six patients in the HIV-positive group with indeterminate results, and the median lymphocyte count was significantly lower. Although no significant difference was found between the median lymphocyte counts of the HIV-positive and HIV-negative group, the positivity rates and secreted interferon (IFN)-ɣ levels were lower, and the indeterminate results were higher in the HIV-positive group than in the HIV-negative group, but the difference was not significant. The rate of QFT-Plus positivity was 32.4% in patients with a viral load below 10,000 copies/ml and 16.1% in patients with a viral load above 10,000 copies/ml (p=0.047). Conclusion: The positivity rates and secreted IFN-ɣ levels were lower, and the indeterminate results were higher in the HIV-positive group than in the HIV-negative group. The addition of TB2 tube to the QFT-Plus assay could contribute to the sensitivity of the test in both HIV-positive and HIV-negative individuals with LTBI.